Glass and Ceramics - Sokolova, Lyudmila V.; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
Glass and Ceramics reports on advances in basic and applied research and plant production techniques in glass and ceramics. The journal's broad coverage includes developments in the areas of silicate chemistry, mineralogy and metallurgy, crystal chemistry, solid state reactions, raw materials, phase equilibria, reaction kinetics, physicochemical analysis, physics of dielectrics, and refractories, among others. Glass and Ceramics is a translation of the Russian journal Steklo i Keramika. The Russian Volume Year is published in English from April. All articles are peer-reviewed.
Keywords: Materials science; Ceramics; Glass; Composites (Materials).; Composite materials; Ceramics, Glass, Composites, Natural Materials; Characterization and Evaluation of Materials; Materials Science, general